Long-range transported dust enhances ice nucleating particle abundance in the North China Plain - Yue Sun; Yujiao Zhu; Hengde Liu; Lanxiadi Chen; Hongyong Li; Yujian Bi; Di Wu; Xiangkun Yin; Can Cui; Ping Liu; Yu Yang; Jisheng Zhang; et al. (Journal of Environmental Sciences, 2026)

Advances in carrier-free nanodrug delivery systems - Jin-Ye Liu; Yan-Yan Zheng; Shu-Yu Wang; Yan-Ping Bi; Ming-Shuang Sun; Ji-Fu Hao; Yu-Jing He (Drug Delivery and Translational Research, 2026)

Isolation of Rhizospheric Fungi from Crocus sativus L. Rhizosphere and their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xin-Zhu Yu; Zi-hao Zhu; Xue-Wen Bi; Kun-miao Feng; Ying-jie Lu; Khalid Rahman; Bo Zhu; Lu-ping Qin; Zhen-zhen Zhang; Ting Han (Current Microbiology, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

Probabilistic space-time prisms in road networks with travel time uncertainties - Hui-Ping Chen; Zhi-Chun Li; Bi Yu Chen (Journal of Transport Geography, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Revisiting the Indium Window effect: Insights from sphalerite big data - Qi-Nan Zou; Yu-Miao Meng; Rui-Zhong Hu; Xiao-Wen Huang; Xian-Wu Bi; Tai-Ping Zhao (Journal of Asian Earth Sciences, 2025)

The GLI3 may be involved in the damage process of Eimeria tenella to chicken cecal tissue - Wanjiang Xiang; Ying Chen; Ye He; Yongmei Yu; Ping Li; Bi Wang; Zhentao Cheng (Veterinary Parasitology, 2025)

Metabolomic analysis elucidates the dynamic changes in aroma compounds and the milk aroma mechanism across various portions of tea leaves during different stages of Oolong tea processing - Bi-Heng Wang; Ping-Hsiu Huang; Chih-Yu Lo; Wen-Chang Chang (Food Research International, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Mechanisms of intermittent theta-burst stimulation attenuating nerve injury after ischemic reperfusion in rats through endoplasmic reticulum stress and ferroptosis - Xin-Ya Shen; Xing-Yu Zhang; Ping-Ping Han; Yi-Ning Zhao; Guo-Hui Xu; Xia Bi (Molecular Biology Reports, 2024)
Background Repetitive transcranial magnetic stimulation (rTMS) exerts neuroprotective effects early in cerebral ischemia/reperfusion (I/R) injury. Intermittent theta-brust stimulation (iTBS), a more time-efficient modality of rTMS, improves the efficiency without at least decreasing the efficacy of the therapy. iTBS elevates cortical excitability, and in recent years it has become increasingly common to apply iTBS to patients in the early post-IS period. However, little is known about the neuroprotective mechanisms of iTBS. Endoplasmic reticulum stress (ERS), and ferroptosis have been shown to be involved in the development of I/R injury. We aimed to investigate the potential regulatory mechanisms by which iTBS attenuates neurological injury after I/R in rats. Methods Rats were randomly divided into three groups: sham-operated group, MCAO/R group, and MCAO/R + iTBS group, and were stimulated with iTBS 36 h after undergoing middle cerebral artery occlusion (MCAO) or sham-operated. The expression of ERS, ferroptosis, and apoptosis-related markers was subsequently detected by western blot assays. We also investigated the mechanism by which iTBS attenuates nerve injury after ischemic reperfusion in rats by using the modified Neurological Severity Score (mNSS) and the balance beam test to measure nerve function. Results iTBS performed early in I/R injury attenuated the levels of ERS, ferroptosis, and apoptosis, and improved neurological function, including mNSS and balance beam experiments. It is suggested that this mode of stimulation reduces the cost per treatment by several times without compromising the efficacy of the treatment and could be a practical and less costly intervention.

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Evaluation of energy-environmental-economic benefits of CNG taxi policy using multi-task deep-learning-based microscopic models and big trajectory data - Bi Yu Chen; Qi Liu; Weishu Gong; Jia Tao; Hui-Ping Chen; Fu-Rong Shi (Travel Behaviour and Society, 2024)

A new hybrid PM$$_{2.5}$$ volatility forecasting model based on EMD and machine learning algorithms - Ping Wang; Xu Bi; Guisheng Zhang; Mengjiao Yu (Environmental Science and Pollution Research, 2023)

The impacts of spatio-temporal variation of natural and agricultural influences on the environmental water quality in a fluvial-lacustrine watershed in China - Yu Feng; Bing-Hui Zheng; Hai-Feng Jia; Bing-Bing Song; Yang Liu; Jun-Ping Bi (Environmental Science and Pollution Research, 2023)

D-π-A array structure of Bi4Ti3O12-triazine-aldehyde group benzene skeleton for enhanced photocatalytic uranium (VI) reduction - Xin Liu; Rui-Xiang Bi; Feng-Tao Yu; Cheng-Rong Zhang; Qiu-Xia Luo; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Purification performance from bypass ecological treatment systems treating WWTPs effluents and improvement of water quality in receiving rivers: A case study in southern China - Xiaoxu Zheng; Shengjun Xu; Yeliang Bi; Gong Cheng; Shuanglong Ma; Hao Zhang; Cancan Jiang; Cong Wang; Ping Lyu; Yu Qin; Xuliang Zhuang (Journal of Environmental Management, 2023)

Pre exposure to enriched environment alleviates brain injury after ischemia-reperfusion by inhibiting p38MAPK/STAT1 pathway - Xin-Ya Shen; Yu Han; Zhen-Kun Gao; Ping-Ping Han; Xia Bi (Molecular Biology Reports, 2023)
Background Stroke is one of the major diseases that endangers human health. It is widely reported that enriched environment (EE) can improve the neurological function in different brain injury models. Recently, relevant researches have indicated that MAPK pathway is closely related to the inflammatory response in nervous system related diseases. However, whether pre exposure to EE (EE pretreatment) has a preventive effect, and its mechanism are not clear. Therefore, this study aimed to determine the possible benefits and related mechanisms of EE in preventing brain injury after acute ischemia-reperfusion. Methods Adult Sprague Dawley rats were kept in enriched or standardized environments for 21 days. Then the middle cerebral artery of rats was occluded for one hour and 30 min, and then reperfusion was performed. Then their neurological deficit score was evaluated. Cerebral edema, along with ELISA and protein quantities of p38MAPK, JNK, ERK, IL-1β, TNF-α, and co-localization of Iba1 were assessed. Changes in neuroinflammation and apoptosis were also detected in the penumbra cortex. Results Our research showed that EE pretreatment significantly alleviated acute cerebral ischemia-reperfusion injury in rats. Including the reduction of brain edema and apoptosis, and the improvement of neurological scores. In addition, the protein level of p38MAPK was significantly down regulated in EE pretreatment group, and the downstream protein STAT1 had the same trend. In addition, immunofluorescence results showed that Iba1 in EE pretreatment group decreased, the ELISA results showed that the classical proinflammatory cytokines increased significantly, while anti-inflammatory cytokines in EE pretreatment group increased, and the same results were obtained by Western blot analysis. Conclusion On the whole, our research demonstrated that EE pretreatment can have a protective effect on the organism by inhibiting the p38 MAPK/STAT1 pathway. Thus, EE can be one of the most promising means of disease prevention. Secondly, p38MAPK/STAT1 pathway may be a latent target for the prevention of acute ischemic stroke.

Diverse grouping and mating strategies in the Critically Endangered Hainan gibbon (Nomascus hainanus) - Ping Li; Paul A. Garber; Yu Bi; Kun Jin; Xuming Qi; Jiang Zhou (Primates, 2022)
Understanding flexibility in the social structure and mating strategies of the world’s last remaining population (35 individuals) of wild Hainan gibbons ( Nomascus hainanus ) is critical for developing effective management plans to aid in their population recovery. Three of the five remaining Hainan gibbon groups (A, B, and C) currently live in a social unit characterized by two or three adult males, two reproducing adult females, and offspring. A fourth group (D) contains one adult male, two adult females, and offspring, and Group E contains a single adult male–adult female pair with a young infant. In this study, we describe observations of copulations between multiple resident males and one of the two resident females in Group C. Group C is best described as a small multi-male/multi-female group. We found that this breeding female (F2) solicited copulations from two resident adult males (M1 and M2) on the same day, and also mated with each of these two males on different days. Resident males were not observed to interrupt the mating pair. Although factors such as a biased adult sex ratio, severe population disruption, and habitat degradation can help explain variation in group composition and mating strategies in Hainan gibbons, we argue that there exists considerable mating system variability across gibbon species, and that this variability offers important insights into male and female Hainan gibbon group structure and reproductive strategies.

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Transcriptome analysis reveals genes associated with leaf color mutants in Cymbidium longibracteatum - Jiang Yu; Wang Qiang; Shen Qin-Qin; Zhuo Bi-Ping; He Jun-Rong (Tree Genetics & Genomes, 2020)

The role of MAPK signaling pathway in formation of EMT in oral squamous carcinoma cells induced by TNF-α - Xiao-Wei Zhao; Jing-Ping Zhou; Yu-Lan Bi; Jia-Ying Wang; Rui Yu; Chao Deng; Wei-Kang Wang; Xian-Zhen Li; Rui Huang; Jili Zhang; De-Tao Tao (Molecular Biology Reports, 2019)

Characteristics of agro-meteorological disasters and their risk in Gansu Province against the background of climate change - Ying Wang; Qiang Zhang; Su-Ping Wang; Jin-Song Wang; Yu-bi Yao (Natural Hazards, 2017)

Antioxidant activity of alcohol aqueous extracts of Crypthecodinium cohnii and Schizochytrium sp. - Jin-hui Yu; Yu Wang; Jie Sun; Fei Bian; Gao Chen; Yan Zhang; Yu-ping Bi; Ying-jie Wu (Journal of Zhejiang University-SCIENCE B, 2017)

Effects of short-term inflammatory and/or hypoxic pretreatments on periodontal ligament stem cells: in vitro and in vivo studies - Yang Yu; Chun-Sheng Bi; Rui-Xin Wu; Yuan Yin; Xi-Yu Zhang; Ping-Heng Lan; Fa-Ming Chen (Cell and Tissue Research, 2016)

Activation of phenylpropanoid pathway and PR of potato tuber against Fusarium sulphureum by fungal elicitor from Trichothecium roseum - Xiao-yan Yu; Yang Bi; Lu Yan; Xiao Liu; Yi Wang; Ke-ping Shen; Yong-cai Li (World Journal of Microbiology and Biotechnology, 2016)

Sex identification and genetic variation of Saccharina (Phaeophyta) gametophytes as revealed by inter-simple sequence repeat (ISSR) markers - Jun-Gang Gu; Yu-Ping Sun; Yu Liu; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2014)

Curcumin promotes cholesterol efflux from adipocytes related to PPARgamma–LXRalpha–ABCA1 passway - Shao-zhuang Dong; Shui-ping Zhao; Zhi-hong Wu; Jun Yang; Xiang-zhu Xie; Bi-lian Yu; Sai Nie (Molecular and Cellular Biochemistry, 2011)

Isolation and expression analysis of LEA genes in peanut (Arachis hypogaea L.) - Lei Su; Chuan-Zhi Zhao; Yu-Ping Bi; Shu-Bo Wan; Han Xia; Xing-Jun Wang (Journal of Biosciences, 2011)

Lack of association between methylenetetrahydrofolate reductase gene A1298C polymorphism and breast cancer susceptibility - Li-Xin Qiu; Jian Zhang; Wen-Hua Li; Qun-Ling Zhang; Hui Yu; Bi-Yun Wang; Lei-Ping Wang; Jia-Lei Wang; Hui-Jie Wang; Xiao-Jian Liu; Zhi-Guo Luo; Xiang-Hua Wu (Molecular Biology Reports, 2011)

Comparative temporal analyses of the Pinus sylvestris L. var. mongolica litv. apical bud proteome from dormancy to growth - Ying-Dong Bi; Zhi-Gang Wei; Zhuo Shen; Tian-Cong Lu; Yu-Xiang Cheng; Bai-Chen Wang; Chuan-Ping Yang (Molecular Biology Reports, 2011)

Characterization of Five Putative Acyl Carrier Protein (ACP) Isoforms from Developing Seeds of Arachis hypogaea L. - Meng-Jun Li; Xing-Jun Wang; Lei Su; Yu-Ping Bi; Shu-Bo Wan (Plant Molecular Biology Reporter, 2010)

Isolation and Characterization of Putative Acetyl-CoA Carboxylases in Arachis hypogaea L. - Meng-Jun Li; Han Xia; Chuan-Zhi Zhao; Ai-Qin Li; Chang-Sheng Li; Yu-Ping Bi; Shu-Bo Wan; Xing-Jun Wang (Plant Molecular Biology Reporter, 2010)

Cloning and sequence analysis of putative type II fatty acid synthase genes from Arachis hypogaea L. - Meng-Jun Li; Ai-Qin Li; Han Xia; Chuan-Zhi Zhao; Chang-Sheng Li; Shu-Bo Wan; Yu-Ping Bi; Xing-Jun Wang (Journal of Biosciences, 2009)